Efficient workflow scheduling in cloud computing for security maintenance of sensitive data. (28th November 2019) - S., Shahul Hammed; Arunkumar, B.
Summary: The seamless conveying of information's considering internet as a virtual space, connecting all users from the world is cloud computing. In simpler terms it is a means of storing and accessing information over internet irrespective of place and time. The cloud proceeds with the process of storing, retrieving and allowing access, on demand as a paid service. As the benefits of cloud is attractive, the number of users adopting to the cloud also increases, so the workflow management becomes tedious and more challenging in the cloud. The decision to provide with an enhanced work flow management requires proper scheduling recollecting value of the information. So the paper proposes with an efficient method of managing the work flow considering the value of the information by categorizing between the much value and non‐value information's and framing the algorithm that functions as scheduler using the parallel implementation in natural process of genetic algorithm (GA) with secured frame work for the information's of high value. The proposed work shows an overwhelmed performance than the conventional techniques in the time taken for the execution and its total cost. The performance of the scheduler is validated in the WORKFLOWSIM on the grounds of time of execution and total cost. Abstract : The paper proposes with an efficient method of managing the workflow considering the value of the information by categorizing between the much value and non‐value information'sand framing the algorithm that functions as scheduler using the parallel implementation in the natural process of genetic algorithm(GA) with the secured framework for the information's of high value.